Probiotics Current Knowledge and Future Prospects - Enany, Shymaa (IntechOpen, 2018)
Probiotic has been used for centuries especially in fermented dairy products since Metchnikoff associated the intake of fermented milk with prolonged life. Probiotics confer many health benefits to humans, animals, and plants when administered in proper amounts. These benefits include the prevention of gastrointestinal infections and antibiotic-associated diarrhea, the reduction of serum cholesterol and allergenic and atopic complaints, and the protection of the immune system. Furthermore, the proper usage of probiotics could suppress Helicobacter pylori infection and Crohn's disease, improve inflammatory bowel disease, and prevent cancer. In this book, we present specialists with experience in the field of probiotics exploring their current knowledge and their future prospects.